Assessing Land Use and Land Cover Change and Farmers’ Perceptions of Deforestation and Land Degradation in South-West Côte d’Ivoire, West Africa - Jean-Luc Kouassi; Amos Gyau; Lucien Diby; Yeboi Bene; Christophe Kouamé (Land, 2021)
Deforestation and land degradation remain two major economic and environmental threats in Côte d’Ivoire. This study assessed land use and land cover (LULC) change and farmers’ perceptions of the drivers and effects of deforestation and land degradation in south-western Côte d’Ivoire. We used remotely sensed data to determine LULC change trends, and a household survey to collect farmers’ perceptions of deforestation and land degradation. A total of 411 households were interviewed using a structured questionnaire and the focus group discussions involved 25 farmers. Landsat image analysis reported a drastic LULC change and a conversion of forestlands into agriculture from 1987 to 2015 at a rate of 1.44%/year and 3.44%/year for dense forests and degraded forests, respectively. The household survey revealed that the major causes of deforestation perceived by farmers included population growth (79.3%), extensive agriculture (72.9%), migration (54.2%) and logging (47.7%). Land degradation evolved, from a shortened fallow period (46.7%) and an inappropriate application of inputs (31.4%). The perceived major effects linked to deforestation encompassed land degradation (70.6%), loss of biodiversity (63.8%), global warming (56.9%) and loss of livelihood assets (54.3%). Therefore, this study recommends participatory landscape planning, reforestation and capacity building of stakeholders for sustainable intensification of the production systems to reduce LULC challenges for enhanced productive and protective functions of remaining forests.